Impact of telepharmacy services as a way to increase access to asthma care. (21st October 2017) - Brown, Wendy; Scott, David; Friesner, Daniel; Schmitz, Tara
ABSTRACT: Objective : To demonstrate that real-time, telepharmacy-based asthma educational services are feasible and to support the efforts of local primary care prescribers to improve patient outcomes. Methods : The lead investigator (a pharmacist, physician assistant, and certified asthma educator) identified an independent community pharmacy with telehealth capabilities in a rural area with a high prevalence of asthma. Working with the pharmacy, an asthma education program was developed based on the National Asthma Education and Prevention Program guidelines. It consisted of three monthly education visits, with subsequent visits every three months for one year. The Asthma Control Test (ACT) was administered at baseline and at each visit to assess a patient's perception of asthma control. Results : Eighteen of 20 patients (90%) with reversible airway disease completed all six visits in this year-long study. For the 18 patients, the mean ACT scores of 18 at baseline (initiation of intervention) did not meet the threshold for "well-controlled" asthma. By the third educational visit (3 months), 16 patients met ACT criteria for well-controlled asthma (mean score = 20), and they maintained control for the remaining 9-month follow-up period (ACT ≥ 21). Local prescribers authorized medication changes recommended by the asthma educator 20 times and also requested six direct consults with the asthma educator over the study period. Conclusion : Using the local community pharmacy as a vehicle to deliver asthma education services by telepharmacy was utilized by local prescribers. The findings show this is an effective means to engage patients to gain and maintain asthma control.